2011
DOI: 10.1208/s12249-011-9660-8
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Influence of Experimental Conditions on In Vitro Drug Release from Immediate-Release Tablets of Levothyroxine Sodium and Its Relation to Oral Bioavailability

Abstract: The aim of this study was to investigate the influence of experimental conditions on levothyroxine sodium release from two immediate-release tablet formulations which narrowly passed the standard requirements for bioequivalence studies. The in vivo study was conducted as randomised, single-dose, two-way cross-over pharmacokinetic study in 24 healthy subjects. The in vitro study was performed using various dissolution media, and obtained dissolution profiles were compared using the similarity factor value. Drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…However, the dissolution time does not fully explain the subsequent absorption rate. In fact, Kocic et al (119) have shown that the dissolution rate and the absorption rate in the first two hours may diverge, indicating that dissolution does not greatly influence the absorption of levothyroxine in the period of time (1.66 hours) in which the maximal absorption take place (37). Noticeably, a better absorption of thyroxine has been observed in patients simultaneously taking vitamin C (120, 121) which may lower gastric pH in patients with impaired acid secretion (109).…”
Section: Drugs Interference At Gastric Levelmentioning
confidence: 99%
“…However, the dissolution time does not fully explain the subsequent absorption rate. In fact, Kocic et al (119) have shown that the dissolution rate and the absorption rate in the first two hours may diverge, indicating that dissolution does not greatly influence the absorption of levothyroxine in the period of time (1.66 hours) in which the maximal absorption take place (37). Noticeably, a better absorption of thyroxine has been observed in patients simultaneously taking vitamin C (120, 121) which may lower gastric pH in patients with impaired acid secretion (109).…”
Section: Drugs Interference At Gastric Levelmentioning
confidence: 99%
“…This bioequivalence study was divided into 2 separate trials in which the timing of drug administration differed: fasting administration and postprandial administration. In both trials, a single‐center, randomized, open‐label, single‐dose, 2‐formulation, 2‐period, 2‐sequence crossover design, and a 14‐day washout period were adopted 9 …”
Section: Methodsmentioning
confidence: 99%
“…Based on the solubility and the permeability rates high or low, drugs are in fact classified into one of four categories of the BCS. This has been proven difficult for levothyroxine sodium since there are sources classifying it as belonging to each of the abovementioned classes ( 26 , 27 ). Interestingly, also the formation of large aggregates in aqueous media may enable the compound to reach concentration even higher than 15 mg/100 ml ( 26 ).…”
Section: Levothyroxine Structurementioning
confidence: 99%